Numerical modelling of the quasi-brittle behaviour of refractory ceramics by considering microcracks effect. Issue 3 (March 2022) - Asadi, Farid; André, Damien; Emam, Sacha; Doumalin, Pascal; Huger, Marc
Abstract: In the steelmaking industry, the inner lining of ladles is made of refractory ceramics, which are constantly subjected to thermal shocks during their service. Experimentally, it is observed that pre-existing microcracks could significantly increase the thermal shock resistance of these ceramics. The presence of such microcracks network within the refractory microstructure could lead to a non-linear quasi-brittle mechanical behaviour. To model this quasi-brittle behaviour, a suitable numerical approach is the Discrete Element Method (DEM), which can circumvent the limitations of more conventional continuum approaches in capturing microstructural effects required to simulate multi-fracture propagation. Here, it is aimed to simulate such quasi-brittle behaviour by initial well-distributed damages, with a strength dispersion following a Weibull distribution. In this way, the microcracks effect on the quasi-brittle behaviour of a numerical sample under uniaxial and cyclic tensile tests is investigated. Ultimately, a quantitative DEM model to simulate such a complex behaviour is proposed.